Co-exposure to multiple metals, TERT-CLPTM1L variants, and their joint influence on leukocyte telomere length. (July 2020) - Bai, Yansen; Fu, Wenshan; Guan, Xin; Wu, Xiulong; Li, Guyanan; Wei, Wei; Feng, Yue; Meng, Hua; Li, Hang; Li, Mengying; Fu, Ming; Jie, Jiali; et al.
Highlights: Increased plasma manganese level is positively associated with telomere length. Multipollutant associations suggest manganese as a sole predictor for telomere length. Manganese has joint effects with TERT-CLPTM1L variants on increasing telomere length. This study offered clues for the early prevention of telomere shortening related diseases. Abstract: Objective: Telomere is required for maintaining chromosome stability and genome integrity, while telomere length is sensitive to environmental stressors. We aimed to identify the effects of multiple metals co-exposure as well as their joint effects with TERT-CLPTM1L variants on leukocyte telomere length (LTL). Methods: This study included 842 workers from a coke-oven plant, of whom plasma concentrations of 23 metals and LTL were determined. Genetic variations in TERT-CLPTM1L were genotyped by using the Global Screening Array. Multipollutant-based statistical methods, including the Bonferroni-correction, backward elimination procedure, and LASSO penalized regression analysis, were used to select the LTL-associated metals. Generalized linear regression models were used to evaluate the joint effects of TERT-CLPTM1L variants with positive metal on LTL. Results: Each 1% increase in plasma concentration of manganese (Mn) was significantly associated with a 0.153% increase in LTL [β(95%CI) = 0.153(0.075, 0.230), P  < 0.001] in single-metal models after Bonferroni-correction. The multiple-metal models and the LASSO penalized regression analysis both indicated Mn as the sole significant predictor for LTL. Furthermore, 5 tagSNPs (rs33954691, rs6554759, rs465498, rs2455393, and rs31489) in TERT-CLPTM1L with high plasma Mn (>4.21 μg/L) showed joint effects on increasing LTL. Conclusions: Our study revealed the independent and positive association between plasma Mn and LTL when accounting for co-exposure to other metals. This effect can be further enhanced by TERT-CLPTM1L variants. These results may advance our understanding of the complex interplay between genetic and environmental factors on telomere length. Further experimental studies are warranted to elucidate the underlying mechanisms.